2017
DOI: 10.1177/0954405417718594
|View full text |Cite
|
Sign up to set email alerts
|

Boundary condition for deformation wear mode material removal in abrasive waterjet milling: Theoretical and experimental analyses

Abstract: Producing quality features with abrasive waterjet milling requires the generation of shallow kerfs with low surface waviness. Typically, such kerfs are produced by deformation wear mode of material removal realized with certain combination of process parameters chosen based on an elaborate experimental analysis. Instead, these parameters can be selected through a modeling methodology developed based on deformation wear erosion theory. As a first part of this development, it is essential to identify the conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…where x, y , and z are the coordinates referring to the abrasive jetting origin in accelerator tank, t the time, ρ a the air density, ρ w the water density, H the acceleration of mass point in the air, D the diameter of abrasive grit, and C is a drag coefficient expressed as the function of Reynolds number based on the concentrated stream and the kinematic viscosity of air. 24…”
Section: Multi-phase Flow Models and Stream Effectiveness Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…where x, y , and z are the coordinates referring to the abrasive jetting origin in accelerator tank, t the time, ρ a the air density, ρ w the water density, H the acceleration of mass point in the air, D the diameter of abrasive grit, and C is a drag coefficient expressed as the function of Reynolds number based on the concentrated stream and the kinematic viscosity of air. 24…”
Section: Multi-phase Flow Models and Stream Effectiveness Indexesmentioning
confidence: 99%
“…where x, y, and z are the coordinates referring to the abrasive jetting origin in accelerator tank, t the time, r a the air density, r w the water density, H the acceleration of mass point in the air, D the diameter of abrasive grit, and C is a drag coefficient expressed as the function of Reynolds number based on the concentrated stream and the kinematic viscosity of air. 24 Since abrasive jetting stream is very difficult to be measured directly, typical flow models should be used for flow demonstration and principle investigation in practices, to study their constructive influences on the prediction of stream effectiveness, with the k-e, k-e-R t , Spalart-Allmaras, Reynolds stress, and large-eddy simulation (LES) models be focused sequentially. 25 Besides, some calibration properties selected out as the qualified mathematical indexes calibrating stream effectiveness, such as turbulence RMS velocity (V RMS , m/s), turbulence intensity (T i ), turbulence kinetic energy (T c , kJ), turbulence entropy (T e , J/K), and Reynolds shear stress (R s , kPa), 26 are employed to quantify abrasive jetting stream thanks to their clear illustrations of physical properties and working effectiveness of multi-phase turbulence and keep independent from external signals or environmental interference.…”
Section: Multi-phase Flow Models and Stream Effectiveness Indexesmentioning
confidence: 99%
“…2 AWJ was initially utilized for linear cutting of plates, but it has kept evolving to performing controlled depth processes such as milling and turning. 3 Hashish 4 reported that abrasive waterjet turning (AWJT) can efficiently turn carbide-metal composites, glass, and ceramics. This process exploits the eroding action of AWJ to produce axisymmetric workpieces using the same principles of centre lathe turning where the AWJ replaces the traditional tool insert.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction of depth of cut in MMCs has been carried out using theoretical models [12], empirical models [13] and semi-empirical models [14]. Theoretical models are difficult to develop in the case of MMCs because they depend on the equations that govern the physics associated with the cutting process.…”
Section: Introductionmentioning
confidence: 99%